2023
DOI: 10.3390/su15108184
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Produce Supply Chain Coordination Based on Freshness Preservation Strategy

Abstract: Today, consumers are increasingly demanding higher quality in fresh agricultural products. The issues that need to be addressed now are how to keep fresh products fresh and how to coordinate the operations of supply chain participants. Three decision models are developed in this paper using the Stackelberg model: supplier-led decision making, retailer-led decision making, and centralized decision making. The comparative model analysis shows the following: (1) Regardless of the decision model, the supply chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…In addition to the buyback contract and wholesale price contract mentioned in the above literature, there are many other common contracts in the research. Examples include quantity flexibility contract [6], revenue sharing contract [7] [8], cost sharing contract [9], [10], quantity discount contract [11], option contract [12], [13], and sales rebate contract [14]. The study found that these contracts can help improve supply chain performance [4], [15], [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the buyback contract and wholesale price contract mentioned in the above literature, there are many other common contracts in the research. Examples include quantity flexibility contract [6], revenue sharing contract [7] [8], cost sharing contract [9], [10], quantity discount contract [11], option contract [12], [13], and sales rebate contract [14]. The study found that these contracts can help improve supply chain performance [4], [15], [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…, which can be further obtained using (10) and (11), Finally, the sales price of the two periods in the formula and simplifying the organization can be obtained using (9).…”
Section: Appendix Amentioning
confidence: 99%
“…The demand for fresh products is declining exponentially over time. Scholars have presented several ways to improve the freshness level [42,43]. Due to the new retail as a new concept, there is a dearth of research investigating the coordination of new retail fresh products' supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a large country producing and selling fresh agricultural products, China is also one of the largest carbon emission countries in the world [ 8 ]. At the same time, fresh agricultural products have the characteristics of easy deterioration and seasonality [ 9 12 ], their preservation has become a difficult problem in the process of production, transportation and sales [ 13 , 14 ]. With the intensification of the national market competition and the improvement of low-carbon awareness, the fresh agricultural products industry urgently needs to expand the low-carbon market, so reducing carbon emissions and expanding the market demand for fresh agricultural products is one of the issues worthy of in-depth research [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%